The Relationship Between Indonesia’s Foreign Direct Investment and Bilateral Intra-Industry Trade with Japan, China, and ASEAN-9 - Suhaila Marisa; Ichihashi Masaru (Jurnal Ekonomi & Kebijakan Publik, 2021)
Many countries try to engage more in international trade to be part of global networks. Foreign investment is one of the ways to improve a country’s economies of scale. Thus, developing countries, such as Indonesia, try to attract more FDI. FDI is mainly export oriented and wants to compete globally. Intra-industry trade measures export and import in the same industry. A high degree of intra-industry trade means a country has strong integration with a partner’s country. This study examines the relationship between FDI in Indonesia’s manufacturing sector and bilateral intra-industry trade between Indonesia and Japan, China, and ASEAN-9, especially at the industry level. The method of this study is the Fixed Effect Model. The result shows that the linkage between FDI and intra-industry trade is only significant in specific industries. In the case of Indonesia and Japan, FDI in the vehicle and other transportation industry has the highest correlation with intra-industry trade. Meanwhile, in the case of Indonesia and China, FDI in the metal, except machinery, and equipment industry shows the highest association with intra-industry trade. In the case of Indonesia and ASEAN-9, the highest linkage between FDI and intra-industry trade is in the textile industry. The relationship between FDI and intra-industry trade differs across locations and industries.Keywords: foreign direct investment, manufacture, intra-industry tradeAbstrakBeberapa negara mencoba untuk lebih terlibat dalam perdagangan internasional untuk menjadi bagian dari jaringan global. Investasi asing dipercaya merupakan salah satu cara untuk meningkatkan skala ekonomi dari suatu negara. Oleh karena itu, negara berkembang seperti Indonesia mencoba untuk menarik lebih banyak penanaman modal asing (PMA). Tujuan utama PMA biasanya adalah berorientasi ekspor dan ingin bersaing di pasar global. Perdagangan intraindustri mengukur ekspor dan impor dalam satu kategori industri. Indeks perdagangan intraindustri yang mempunyai nilai tinggi berarti suatu negara memiliki integrasi yang kuat dengan negara mitra. Kajian ini mencoba menganalisis hubungan antara PMA sektor manufaktur di Indonesia dan bilateral perdagangan intraindustri antara Indonesia dengan masing-masing Jepang, China, dan ASEAN-9, khususnya pada level industri. Metode dari penelitian ini menggunakan Fixed Effect Model. Hasil penelitian menunjukkan bahwa keterkaitan antara PMA dan perdagangan intraindustri hanya signifikan pada industri tertentu. Dalam kasus Indonesia dan Jepang, PMA pada industri kendaraan bermotor dan alat transportasi lain memiliki korelasi tertinggi dengan perdagangan intraindustri. Sedangkan untuk kasus Indonesia dan China, PMA pada industri logam dasar, barang logam, bukan mesin dan peralatannya menunjukkan hubungan yang paling tinggi dengan perdagangan intraindustri. Dalam kasus Indonesia dan ASEAN-9, hubungan tertinggi antara PMA dan perdagangan intraindustri adalah pada industri tekstil. Hubungan PMA dan perdagangan intraindustri berbeda antarlokasi dan industri.Kata kunci: penanaman modal asing, manufaktur, perdagangan intraindustri